Firefighters’ occupational exposure to air pollution: impact on COPD and asthma—study protocol - Joana V Barbosa; Pedro T B S Branco; Maria C M Alvim-Ferraz; Fernando G Martins; Sofia I V Sousa (BMJ Open Respiratory Research)
Introduction Firefighting continues to be among the most hazardous yet least studied occupations in terms of the impact of exposure to occupational disease. In particular, firefighters are at increased risk of adverse health effects due to exposure to significant levels of potentially harmful substances, namely carbon monoxide, particulate matter and formaldehyde, during their professional duties.This paper reports an epidemiologic study aiming to reduce the gaps in assessing the long-term effects of air pollution exposure to forest fires’ combat on firefighters, namely regarding chronic obstructive pulmonary Disease (COPD) and asthma.Methods and analysis Based on the implementation in an area with high forest fires (in Portugal), the study will analyse firefighters’ exposure to fire emissions by measuring air pollutants with personal exposure monitors during forest fire combat through a retrospective cohort study (exposed vs non-exposed). Moreover, based on answers to validated questionnaires and medical examinations to be performed by medical doctors, the study will assess the prevalence, incidence and exacerbation of COPD and asthma in firefighters, thus considering both short-term and long-term effects. Based on the results above referred, the study aims to evaluate the impact of exposure and inhalation dose of air pollutants during forest fires’ combat on the development of the above-referred chronic diseases. The approximate number of participants in the study will never be less than 186, guaranteeing 80% of study power (significant at a 5% level).Ethics and dissemination The study has been approved by the Ethical Committee of Centro Hospitalar Universitário São João. The results will be published in international and national journals and conferences, allowing the results obtained to be communicated to the scientific community. Moreover, up-to-date data will be disseminated to stakeholders and decision-makers to help them decide on triggering official control measures.